Advances in the treatment of follicular lymphoma. (February 2015) - Ujjani, Chaitra; Cheson, Bruce D
<x xml:space="preserve">Abstract</x> Introduction: Follicular lymphoma, the most common of the indolent non-Hodgkin lymphomas, exhibits a highly variable clinical course. The disease is characterized by a high response rate to therapy, but due to repeated relapses additional treatment options are necessary. Areas covered: The rediscovered chemotherapeutic agent, bendamustine, has demonstrated remarkable efficacy and tolerability when paired with rituximab and has been established as a front-line regimen. More recently, a number of new targeted therapies have been developed, directed against intrinsic drivers of malignant B-cell proliferation and survival, and extrinsic factors such as the tumor microenvironment and escape from the immune response. For the first time, a targeted oral agent, idelalisib, is now FDA approved for the treatment of this disease. Expert opinion: The promise of these new therapies has enabled us to move forward with multi-targeted biologic regimens and toward a future of individualized treatment without traditional chemotherapy.